Overall survival in myelodysplastic syndromes: a cohort study - Tatjana Sotirova; Oliver Karanfilski; Sonja Genadieva Stavric; Svetlana Krstevska; Marica Pavkovic; Gazmend Amzai (Quest Journals, 2014)
Factors like age, gender, FAB subtypes, cytopenias, proportion of bone marrow (BM) blasts, comorbidities, transfusion dependence, albumins, lactate dehydrogenase (LDH), karyotype abnormalities and molecular biomarkers can refine the prediction of prognosis in MDS. The aim of this study was to evaluate factors that influence overall survival (OS) in MDS. We conducted retrospective cohort study of 184patients (98 male, 86 female) with MDS who presented to the University Clinic of Hematology, Skopje, Macedonia, from January 2011 to October 2014. The differences in OS between male and female were not significant (p = .08368). The mean age at diagnosis was 66,5 years. Differences in OS among FAB subtypes were significant (p = .00117). OS inversely correlated with BM blast percentage (p = .00054). Hemoglobin, platelets and absolute neutrophil count (ANC) did not influence OS - p=0.107161, (p= .79288) and (p= .94860), respectfully. Ferritin (p = .63575), LDH and transfusion (p= .48247) did not influence OS. Albumins and comorbidities influenced OS (p= .01137 and p= .00184, respectfully). We can conclude that FAB subtypes, BM blast percentage, albumins and comorbidities had an influence on OS, while age, gender, hemoglobin, platelet count, ANC, transfusion dependence and LDH had no impact on OS.
Keywords: myelodysplastic syndromes; overall survival; prognostic factors